ADVICE IS A SYNERGIC FACTOR OF CONSENSUS (Scientific journal of the Fergana State University, 2024)
The article analyzes synergistically in consensus decision making. In this process, the contribution of the consultative factor, the effect of the consultative process on consensus, and the procedure are explained scientifically. The role of consensus building in the elimination of conflicts and disputes and the philosophical parts of the organization of consultation and consultation processes in this process are scientifically illuminated.